Movement Regulation of Gymnastics Skills under varying Environmental Constraints - Thomas Heinen (Asociación Española de Ciencias del Deporte, 2018)
Introduction: Gymnasts perform complex skills on stationary apparatuses. The perceived structure of each apparatus in relation to gymnasts' position, orientation and state of motion is one important factor that influences movement regulation. This study targeted the question, how gymnasts regulate complex skills as a function of varying apparatus constraints. Materials and Methods: Trained gymnasts performed three cartwheels in a row under two different experimental conditions of manipulated apparatus constraints (increased and decreased space available on a spring floor in order to perform the cartwheels). Gymnasts' regulation strategy in the different experimental conditions was assessed. Results: Results revealed that gymnasts perfectly accommodated the manipulated apparatus constraints in the two experimental conditions, thereby supporting the note of perception-action coupling operating as a control mechanism when performing complex gymnastics skills under changed apparatus constraints. Distributing regulation between and within the cartwheels was different depending on the manipulation of apparatus constraints, and was related to the anticipated effort when achieving the movement goal. Conclusion: It can be stated that gymnasts regulate complex motor skills in a foreseeable (i.e., stationary) environment in a way that best suits the current situation in order to accommodate the current configuration of apparatus constraints.